2003
DOI: 10.1590/s0074-02762003000100011
|View full text |Cite
|
Sign up to set email alerts
|

Protease activity in Giardia duodenalis trophozoites of axenic strains isolated from symptomatic and asymptomatic patients

Abstract: We have examined by gelatin-SDS-PAGE the protease activity in cell lysates of Giardia duodenalis trophozoites of two axenic strains isolated in Brazil from a symptomatic patient and an asymptomatic carrier , and the reference strain Portland 1 (P1). The proteolysis band patterns showed differences among strains isolated from asymptomatic and symptomatic individuals. The lysate of the strain BTU-10, showed only five hydrolysis bands, while a greater number of bands (10-11 bands) Giardia duodenalis (syn. G. l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
15
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…Together, the data suggest that a soluble heat-labile protein fraction in G. duodenalis trophozoites triggers this SGLT-1-mediated host response. Giardia duodenalis trophozoite proteases play an important role in the microbial-host epithelial interaction during infection ( [Farthing, 1993] and [Guimaraes et al, 2003]). Moreover, protease-activated receptors have been identified on intestinal epithelial cells and are involved in the regulation of cell apoptosis and inflammatory responses ( [Chin et al, 2003] and [Hansen et al, 2005]).…”
Section: Discussionmentioning
confidence: 99%
“…Together, the data suggest that a soluble heat-labile protein fraction in G. duodenalis trophozoites triggers this SGLT-1-mediated host response. Giardia duodenalis trophozoite proteases play an important role in the microbial-host epithelial interaction during infection ( [Farthing, 1993] and [Guimaraes et al, 2003]). Moreover, protease-activated receptors have been identified on intestinal epithelial cells and are involved in the regulation of cell apoptosis and inflammatory responses ( [Chin et al, 2003] and [Hansen et al, 2005]).…”
Section: Discussionmentioning
confidence: 99%
“…At this moment, few studies have identified and characterized trophozoite proteases of strains isolated in endemic areas. Proteolytic activity in trophozoites of two Brazilian axenic strains and the predominance of cysteine proteases were firstly reported by GUIMARÃES et al 3 . More recently, CORADI & GUIMARÃES 2 , employing cell lysates of five strains isolated and axenized in Brazil observed differences in the Giardia proteases ability to hydrolyse different protein substrates and the inhibition of enzymatic activity was substrate dependent.…”
mentioning
confidence: 71%
“…In relation to the intestinal protozoan Giardia, proteases have been characterized and may play role in metabolism and physiologic process such as nutrition, excystation, pathogenesis and evasion of the host immune response [2][3][4][5][9][10][11]15 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we proposed herein the genotyping of five Brazilian axenic isolates obtained from cysts of patients from São Paulo state, for which just proteolytic activity and susceptibility to potential antigiardial agents are available yet (9)(10)(11)(12). For this purpose, we employed PCR amplification of two commonly used genetic markers, the gdh and tpi genes.…”
mentioning
confidence: 99%